ANALISIS HUBUNGAN KUALITAS JASA PELAYANAN DENGAN KEPUASAN PELANGGAN KENTUCKY FRIED CHICKEN (KFC) KANTOR POS DI BANJARMASIN - Rina - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, The purpose of this study is to analyze the relationship of service quality consisting of five dimensions, namely (Empahty, Responsiveness, Reliability, Assurance, Tangible) with customer satisfaction analyze dimension which has the strongest relationship with customer satisfaction KFC post office in Banjarmasin and to analyze level of conformity. The results of this study provide an important conclusion that the five dimensions of service quality (Empahty, Responsiveness, Reliability, Assurance, Tangible) have significant relationship to KFC customer satisfaction, among the five dimensions of service quality, reliability dimension has the strongest relationship with customer satisfaction. The level of customer satisfaction on the service quality that has been given by KFC post office in Banjarmasin is still low so that necessary improvements on dimensions that are still not in accordance with the level of interest of service users so that the user service satisfaction can we achieve maximally.